Integrating Public Relations And Digital Advertising In Telecommunications: Evidence From An Emerging Market Case - Kurnia Dwi Ebthasarie; Rachmat Kriyantono; Bambang Dwi Prasetyo (INJECT (Interdisciplinary Journal of Communication), 2026)
Digital transformation has transformed the way marketing communications work, now requiring strategic collaboration between Public Relations (PR) and digital advertising within an Integrated Marketing Communications (IMC) framework. This study examines the synergistic digital public relations and advertising strategies implemented by Indosat Ooredoo Hutchison (IOH) and their impact on marketing communication effectiveness in the context of digital disruption. A qualitative case study design was used to collect data through comprehensive interviews, cross-channel campaign content analysis, and examination of company documentation. Findings indicate that IOH institutionalized cross-functional collaboration through its Integrated Communications Unit (UKT), which aligns the formulation of PR's strategic narrative with the adaptation of visuals and audiovisuals by digital marketing, ensuring message consistency, cultural relevance, and content harmonization across audience touchpoints. This integration increased brand awareness (with a 42% surge in organic reach), strengthened audience engagement (5.8% above the industry average of 3.2%), and built a more authentic brand perception (+16% positive sentiment). The use of the IMC Alignment Framework after 2022 also increased video completion rates by 21% and the consistency of key visual messages. Conceptually, this research expands the understanding of value-based IMC, positions PR as a brand narrative organizer in an integrated digital communications ecosystem, and offers a practical model of synergy between PR and digital advertising that can be applied in other industries with contextual adjustments.